Enhanced X‑ray Imaging with Gd2O2S:Pr-Epoxy Composite Films: Synthesis, High-Resolution Performance, and Flexibility - Sun, Jinghan; Du, Yongxiao; Luo, Zhaohua; Guo, Hai; Liu, Yongfu; Sun, Peng; Jiang, Jun (ACS applied electronic materials, 2024)
Organic–inorganic composite scintillation films, recognized for their cost-efficiency and tunable scintillation characteristics, have been the subject of extensive research due to their considerable promise for use in X-ray flat panel imaging applications. This study presents a composite scintillation film utilizing Gd2O2S:Pr phosphors, traditional yet effective in this application. By optimizing the solid-state reaction process and employing acid pickling to eliminate impurities, we achieved Gd2O2S:Pr phosphors with pure phase and precise stoichiometric ratios. Subsequently, these phosphors were combined with epoxy resin to fabricate a composite scintillation film, which demonstrated excellent structural uniformity and flexibility. Furthermore, its imaging performance was evaluated under X-ray irradiation, revealing a resolution of 8 line pairs per millimeter. This outcome underscores the substantial promise of our films for advanced X-ray imaging applications, paving the way for future advancements in this domain.